Undertow - Hichens, Joanne (Department of English Language and Literature, 2014)
Miranda Friend, a therapist at a Cape Town psychiatric hospital, wants to reverse herself from the cul-de-sac of her life. At thirty, she is in a dead-end relationship and is working in a hospital which is struggling under new management.